Quantification of cell death and proliferation of patient-derived ovarian cancer organoids through 3D imaging and image analysis - Skorda Aikaterini; Lauridsen Anna Rossberg; Huhtinen Kaisa; Lahtinen Alexandra; Senkowski Wojciech; Oikkonen Jaana; Hynninen Johanna; Hautaniemi Sampsa; Kallunki Tuula (United States, 2025)
Patient-derived organoids (PDOs) are ideal ex vivo model systems to study cancer progression and drug resistance mechanisms. Here, we present a protocol for measuring drug efficacy in three-dimensional (3D) high-grade serous ovarian cancer PDO cultures through quantification of cytotoxicity using propidium iodide incorporation in dead cells. We also provide detailed steps to analyze proliferation of PDOs using the Ki67 biomarker. We describe steps for sample processing, immunofluorescent staining, high-throughput confocal imaging, and image-based quantification for 3D cultures. For complete details on the use and execution of this protocol, please refer to Lahtinen et al. (2023).